Wizja męczeństwa w zeznaniach Marianny Popiełuszko w procesie beatyfikacyjnym ks. Jerzego Popiełuszki - Kindziuk, Milena (Collectanea Theologica, 2018)
In the history of the Church one finds an event wherein a mother was questioned in the beatification process of her son. This occurred in the case of Marianna Popiełuszko, who before the court of beatification in Warsaw in 1997, responded to all the questions put to her in order to assess the life and work of Fr. Jerzy Popiełuszko as a candidate for sainthood by Church authorities. From these testimonies there emerges an interesting picture of the life and death of Fr. Popiełuszko, as well as his faith and steadfastness. It helps to read the true intentions which were of a religious nature that guided him during his activity. Moreover, this confirms the martyrological nature of his death, in which what counts is not only the anguish inflicted, but the reason for one’s achievements. This also demonstrates that martyrdom was the crowning achievement of his life of faith and love, which was associated with forgiveness that is opposed to hatred or vengeance. This vision of martyrdom is consistent with the classical understanding of martyrdom in the Church, which is not limited only to the moment of death, but applies to the entire life of the martyr.